The association between self-reported health, late career transitions and working time modulations in England. Issue 6 (28th November 2019) - Wels, Jacques
Abstract : Purpose: There is an emerging literature focusing on the impact of late career transitions on health, but little is known so far about the role working time modulations might play in explaining older workers' health. The paper aims to discuss this issue. Design/methodology/approach: Using the English Longitudinal Study of Ageing (ELSA) Waves 4–7, the paper assesses the association between the different types of change in working time, the total weekly working hours at baseline and the level of income and the change in Self-perceived health (SPH). The model controls for financial wealth, qualification, gender, age, the sector of activity and self-reported health at baseline. Findings: Respondents who retire have a better SPH compared with those who keep working at constant working time. Those who work long hours benefit more from retiring. Respondents working long hours before being unemployed tend to be less affected by a negative change in SPH. Those who reduce working time by 50 per cent or more and work long hours at baseline have lower probabilities to be affected by a negative change in SPH compared with those who work fewer hours. Finally, low-paid workers are those who benefit the most from retiring or reducing working time. Social implications: Results point out the need to foster working time arrangements for low-paid workers to prevent adverse health impacts. Originality/value: There is a significant association between change in working time and change in self-reported health that has not been examined by previous studies.